Getting high for likes: Exploring cannabis‐related content on TikTok. (24th January 2022) - Rutherford, Brienna N.; Sun, Tianze; Johnson, Benjamin; Co, Steven; Lim, Tong Liang; Lim, Carmen C. W.; Chiu, Vivian; Leung, Janni; Stjepanovic, Daniel; Connor, Jason P.; Chan, Gary C. K.
Abstract: Introduction: With over 1 billion monthly users globally, a third of whom are under 14 years, TikTok's popularity is indisputable. Publicly available cannabis‐related content on this platform may influence perceptions of cannabis use. We aimed to examine how cannabis‐related videos are portrayed on TikTok. Methods: Data were collected from TikTok using hashtag‐based keywords on cannabis‐related videos ( n = 1377). Seven researchers documented video metrics (i.e. views, likes, comments) and independently coded videos for sentiment and theme. Results: After removing duplicates and non‐related content, the final sample contained 881 videos. These videos had a median view count of 518 700 ( SD = ±1 082 905), median likes count of 99 900 ( SD = ±206 647) and median comment count of 931 ( SD = ±2977). Many videos portrayed cannabis use positively (54.14%; collectively viewed 417 million times), with 15.84% of this subset actively depicting cannabis or administration products. The thematic analysis identified seven non‐mutually exclusive themes. Content portraying cannabis use as entertaining or humorous accounted for 71.74% of videos, with a further 42.90% discussing personal cannabis use experiences and 24.63% promoting the social and cultural acceptability of cannabis use. Discussion and Conclusions: Our sample revealed over half of videos portrayed cannabis use positively and none were age restricted. All were publicly accessible through standard web and smartphone applications. With previous research demonstrating that exposure to cannabis‐related content can influence adolescents' attitudes and problematic cannabis use, it is important more effective age restrictions and regulations are introduced to social media platforms.